Marketing Innovation as a Catalyst for Clean Energy Technology Diffusion: A Quantitative Analysis of Market Penetration Strategies - Endah Retno Wuryandari, Nur; Purwanto, Setiyo; Apriani, Ari (Dinasti Publisher, 2024)
Although the global transition to clean energy has become a priority, the diffusion of clean energy technologies still faces significant challenges, especially in terms of market penetration. Marketing innovation is emerging as a potential catalyst for accelerating adoption, but quantitative understanding of its impact is still limited. This study aims to quantitatively analyze the influence of marketing innovation on the diffusion of clean energy technology, with a focus on market penetration among the millennial generation in Jakarta. Using a cross-sectional research design, data was collected through an online survey of 150 millennial respondents, adapting a structured questionnaire from previous studies. Data analysis was carried out using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) approach to test the relationship between marketing innovation variables, consumer awareness, adoption intentions, and clean energy technology market penetration. The results of the research are expected to provide valuable insights for industry players and policymakers in designing effective marketing strategies to accelerate the adoption of clean energy technologies, as well as contributing to the academic literature on innovation diffusion in the context of the energy transition.